Tectonic evolution of two greenstone belts from the Superior Province in Manitoba - Park, R. G.; Ermanovics, I. F. (Canadian Journal of Earth Sciences, 1978)
The Bigstone Lake and Stevenson Lake greenstone belts are two areas of supracrustal rocks surrounded by quartz diorite to granodiorite plutons and by small patches of tonalitic gneiss interpreted as basement to the greenstone belts. The supracrustal sequence is divided into a lower, mainly volcanic, group correlated with the Hayes River Group of Island Lake and an unconformable upper group with roughly equal proportions of sediments and volcanics correlated with the Island Lake 'Series'. The lower group consists of about 4600 m of basaltic and andesitic pillow lavas with minor greywackes and dacitic volcanics. It is partly replaced at the base by the bordering plutons and cut out at the top by the unconformable upper group, which consists of about 2300 m of greywackes, arkoses, and mudstones above a basal conglomerate containing boulders derived from the lower group and from the basement. A further 2100 m of volcanics overlies these sediments.The supracrustal rocks show three phases of deformation. The first, F 1 , produced major northeast–southwest and east–west synclines. S 1 foliation was developed under greenschist facies to low amphibolite facies metamorphism. F 2 produced smaller scale steep east–west folds with a crenulation cleavage. Subsequent deformation resulted in chevron folds and conjugate shear belts.The intrusion of the plutons commenced before the F 1 deformation and partly controlled it, but a further period of plutonic intrusion occurred after F 1 and before F 2 .The north–south compressive stress prevailing during F 2 and later deformation under waning metamorphism implies that the batholiths in the vicinity of the greenstone belts had completely solidified and that the crust was rigid enough to transmit a uniform stress field. The dominance of east–west structural grain in this part of the Superior Province indicates that these conditions were general.